2023
DOI: 10.1002/adhm.202301861
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Microglia Functions by Developed Nano‐Immuno‐Synergist to Ameliorate Immunodeficiency for Malignant Glioma Treatment

Abstract: Resident microglia are key factors in mediating immunity against brain tumors, but the microglia in malignant glioma are functionally impaired. Little immunotherapy has been explored to restore microglial function against glioma. Herein, oleanolic acid (OA) (microglia “restorer”) and DPPA‐1 peptide (immune checkpoint blockade) were integrated on a nano‐immuno‐synergist (DPAM@OA) to work coordinately. The self‐assembled OA core was coated with macrophage membrane for efficient blood‐brain barrier penetration an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 103 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…This result highlighted the essential role of VCAM-1 in mediating cellular uptake and internalization of VLC@Cur-NPs. In addition, we found that a substantial internalized NPs colocalized with EEA-1 (early endosome marker) at 10 min, and subsequently with Rab11 (recycling endosome marker) at 30 min (Figure S7B). Importantly, the NPs predominantly colocalized with Snap23 (recycling endosome/basolateral membrane fusion marker) rather than with Lamp-1 (lysosome/endosome marker) at 60 min.…”
Section: Resultsmentioning
confidence: 99%
“…This result highlighted the essential role of VCAM-1 in mediating cellular uptake and internalization of VLC@Cur-NPs. In addition, we found that a substantial internalized NPs colocalized with EEA-1 (early endosome marker) at 10 min, and subsequently with Rab11 (recycling endosome marker) at 30 min (Figure S7B). Importantly, the NPs predominantly colocalized with Snap23 (recycling endosome/basolateral membrane fusion marker) rather than with Lamp-1 (lysosome/endosome marker) at 60 min.…”
Section: Resultsmentioning
confidence: 99%